Stringy geometry from F‐theory. Issue 4 (21st March 2016) - Massai, Stefano
Abstract : We review the construction of six‐dimensional non‐geometric string compactifications obtained from torus fibrations with T‐duality monodromy. We take a geometric point of view where T‐duality twists are identified with Dehn twists of an auxiliary surface fibered over a two dimensional base. Degenerations of this auxiliary surface define codimension‐two T‐duality defects. For a large class of heterotic defects, we extract the low energy physics by constructing F‐theory duals that admit simple Calabi‐Yau resolutions.